(untitled) (Movimenta (ISSN 1984-4298), 2021)
Aim: to verify the effectiveness of telemonitoring in an early intervention program according to the perception of those responsible for the children and the physiotherapist during the COVID-19 pandemic. Methodology: Cross-sectional study, with 14 family members of the children assisted in the Monitoring and Early Intervention Program for Infants at Risk in the First Three Years of Life and 6 physiotherapists. The Perception of the Responsible People’s Questionnaire Regarding Telemonitoring was applied to the perception of those responsible, and for the perception of physiotherapists the Questionnaire of Perception of Physiotherapist in Relation to Telemonitoring. The data were analyzed descriptively based on the frequency of response. Results: 78.6% of caregivers showed to be totally satisfied with the treatment through telemonitoring, and 100% could observe some improvement in the development of their baby. In relation to physical therapists, 100% recommend telemonitoring during the isolation period and 83.3% recommend the modality in conjunction with face-to-face intervention. Conclusion: The results of this study point to a new format of health care provision that, based on the perception of those responsible, demonstrated positive effects with regard to a possible treatment modality for the studied sample, mainly in such an adverse world scenario, above all, in the Brazilian reality, caused by the COVID-19 pandemic.